Patients’ knowledge about their involvement in clinical trials. A non-randomized controlled trial - Juan-Salvadores, Pablo; Michel Gómez, Marcela Sánchez; Jiménez Díaz, Víctor Alfonso; Martínez Reglero, Cristina; Iñiguez Romo, Andrés (Frontiers in Medicine, 2022)
Background: Nowadays, good clinical practice should be established in human research. Patient’s rights and autonomy must be respected above the interest of the researcher, making mandatory to raise patient’s awareness on the implications of participating in a clinical study. Contrary to popular belief, this is not always the case. This means that, after signing the informed consent form, some patients have difficulties understanding their responsibilities as participants. Methods: This study is a prospective, multicenter, non-randomized controlled trial comparative survey conducted on patients enrolled in a clinical trial to evaluate and improve their understanding after an educational intervention was applied to the research staff. Results: females were underrepresented in the clinical trials performed in this study, 21.5%. Most of the participants had a low educational level (74.4%). Around 5% and 10% of the research participants were not aware they were part of a clinical study, and more 24% just trusted in the medical decision to be enrolled. After the interventional education, the following items: “given time and resolution of the patient doubts” (p-value = 0.003), “enough written information” (p-value = 0.006), “explanation of the risks of participating in the study” (p-value = 0.047) and understanding of the information provided to them showed an improvement regarding the study in which they were participating. Conclusions: the research participants understanding of their involvement in clinical trials is limited. An educational intervention on the research team can improve the process of empowerment and transit of information.